Magnetic resonance imaging correlates of physical disability in relapse onset multiple sclerosis of long disease duration. (January 2014) - Kearney, H; Rocca, MA; Valsasina, P; Balk, L; Sastre-Garriga, J; Reinhardt, J; Ruggieri, S; Rovira, A; Stippich, C; Kappos, L; Sprenger, T; Tortorella, P; et al.
Background: Understanding long-term disability in multiple sclerosis (MS) is a key goal of research; it is relevant to how we monitor and treat the disease. Objectives: The Magnetic Imaging in MS (MAGNIMS) collaborative group sought to determine the relationship of brain lesion load, and brain and spinal cord atrophy, with physical disability in patients with long-established MS. Methods: Patients had a magnetic resonance imaging (MRI) scan of their brain and spinal cord, from which we determined brain grey (GMF) and white matter (WMF) fractional volumes, upper cervical spinal cord cross-sectional area (UCCA) and brain T2-lesion volume (T2LV). We assessed patient disability using the Expanded Disability Status Scale (EDSS). We analysed associations between EDSS and MRI measures, using two regression models (dividing cohort by EDSS into two and four sub-groups). Results: In the binary model, UCCA ( p < 0.01) and T2LV ( p = 0.02) were independently associated with the requirement of a walking aid. In the four-category model UCCA ( p < 0.01), T2LV ( p = 0.02) and GMF ( p = 0.04) were independently associated with disability. Conclusions: Long-term physical disability was independently linked with atrophy of the spinal cord and brain T2 lesion load, and less consistently, with brain grey matter atrophy. Combinations of spinal cord and brain MRI measures may be required to capture clinically-relevant information in people with MS of long disease duration.